Originally Posted by

**dsprice** Using the Laplace transform, solve the initial value problem:

y1’ = -6y1 + 4 y2 (1)

y2’ = -4y1 + 4 y2 (2)

y1(0) = -2

y2(0) = -7

Solving:

(1) becomes: sY1 –y1(0) = -6Y1 + 4Y2 => sY1 +2 = -6Y1 + 4Y2 (3)

(2) becomes: sY2 – y2(0) = -4Y1 + 4Y2 => sY2 + 7 = -4Y1 + 4Y2 (4)

Two equations with 2 unknowns, so starting with (4), we get:

Y1 = [7-(4-s)Y2]/-4

Plugging into (3), we get:

Y2 = [7s+50]/[(s+4)(s-2)]

At this point, I can use partial fractions to determine A/(s+4) and B/(s-2), but I can’t help but think I messed up the math somewhere as I can’t match the stated answer of:

y1(t) = 2e**-4t – 4e**2t

y2(t) = e**-4t – 8e**2t

The (s+4) and (s-2) terms of my answer makes me think I’m tantalizingly close, but any help on where I messed up will be much appreciated.